MENUJU INDUSTRIAL SECURITY DALAM MEWUJUDKAN TENAGA SATPAM PROFESIONAL, MODERN DAN TERPERCAYA DI INDONESIA - Edisah Putra (Maleo Law Journal, 2020)
Global economic growth so that the impact on business competition is so intense and causes the need for security services is needed. Nowadays, the security professionalism of security guards is very important, because industrial security does not only provide physical protection services for installation, security of personnel, security of information and other technical from any security and order disturbances, but also as a protector in the effort to manage risks from various threats to kamtibmas in the business world. Professional, modern and trusted security guards must have skills, intelligence, integrity and discipline. So the problem under study is towards industrial security in realizing professional, modern and trusted security guards in Indonesia. Based on studies with normative juridical research that Security Guards are Police Partners to carry out limited authority functions in accordance with the Police Regulations, where Security Guards are part of enforcing rules and discipline within the company. Thus the protection and legal basis for security guards differ from other workers / laborers. The government is expected to be able to regulate and make legislation on invitations regarding the position of security guards as partners and fostered by the Indonesian police and how to supervise, manage and foster Industrial Security as a Security Services Business Entity. Keywords: industrial security, security unit, legal protection